The relationship between rural endowment insurance and rural human capital investment : a exploratory study of Hebei Province, P. R. China - Yifan, Sun (Penerbit UTM Press, 2013)
In China, Elderly care of rural residents is a heavy burden for Chinese government. The inadequate of rural endowment insurance has resulted in the deficiency of education investment for the next generation, and in some poor families children even lost their chance of going to school. Therefore, it’s necessary to study the relation between rural endowment insurance and human capital. In 2009, a reform has begun. The contribution has been cut into 3 parts, rural residents only need to pay one third; the other 2 parts are paid by the government of the country and local village. 3 years past, this paper used regression analysis to see if the reform improved rural human capital investment, the result showed that there is no significant correlation. The government should do more work on publicity to let rural residents know the policy of new rural endowment insurance, to let them sure that they needn’t worry about their old age life quality.